Metformin promotes anticancer activity of NK cells in a p38 MAPK dependent manner - Wenjiao Xia (Taylor & Francis Group, 2021)
Metformin, a drug prescribed to treat type 2 diabetes, has been reported to possess antitumor activity via immunity activation. However, the influence of metformin on natural killer (NK) cells is not fully understood. Here, we investigated whether metformin exerts a potent anticancer effect by activating NK cells. The results showed that sustained exposure to metformin enhances the cytolytic activity of NK-92 cells. Moreover, this enhancement of cytotoxicity by metformin was also observed in NK cells from healthy peripheral blood and cancer patient ascites. Mechanistically, metformin induced activation of the JAK1/2/3/STAT5 and AKT/mTOR pathways in a p38 MAPK-dependent manner rather than an AMPK-dependent manner. In vivo experiments, metformin also improved cancer surveillance of NK cells in mouse models of lymphoma clearance and metastatic melanoma. Additionally, combination treatment with metformin and anti-PD-1 antibodies increased the therapy response rates of B16F10 melanoma. Moreover, metformin treatment increased NK cell and T cell infiltration in tumors. Therefore, these results provide a deeper understanding of metformin on the effector function of NK cells and will contribute to the development and applications of metformin in cancer treatment strategies.